2017
DOI: 10.1111/scs.12516
|View full text |Cite
|
Sign up to set email alerts
|

Person‐centred climate and psychometrical exploration of person‐centredness and among patients not conveyed by the Ambulance Care Service

Abstract: A highly valid construct of person-centredness exists within nonurgent Ambulance Care Service assignments comprising eight aspects of being taken seriously. The climate in which nonemergency ambulance care is provided has great potential to facilitate person-centredness by means of taking patients seriously. The psychosocial aspects of PCQ-P and person-centredness are somewhat related to each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…Booker, Shaw, and Purdy () suggest strategies to assist patients and bystanders in mitigating their perceptions of risk and state that we should be sensitive to the idea that patients and relatives might not know what type of help they need when they contact emergency care services. Rantala, Forsberg, and Ekwall () highlight that within ambulance care, also and maybe especially, when it is non‐emergency, the care should be person‐centred and always taking patients seriously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Booker, Shaw, and Purdy () suggest strategies to assist patients and bystanders in mitigating their perceptions of risk and state that we should be sensitive to the idea that patients and relatives might not know what type of help they need when they contact emergency care services. Rantala, Forsberg, and Ekwall () highlight that within ambulance care, also and maybe especially, when it is non‐emergency, the care should be person‐centred and always taking patients seriously.…”
Section: Discussionmentioning
confidence: 99%
“…Experience leads to an understanding of different conditions, which shows that both theoretical knowledge and experience are needed to optimize the assessment. Breeman, Poublon, Verhofstad, and Lieshout (2018) Rantala, Forsberg, and Ekwall (2018) highlight that within ambulance care, also and maybe especially, when it is non-emergency, the care should be person-centred and always taking patients seriously.…”
Section: Discussionmentioning
confidence: 99%
“…The meaning of taking patients seriously and the impact when this phenomenon is absent has previously been reported by Rantala, Ekwall and Forsberg [13]. Further research on the concept has resulted in a tentative PREM instrument, the Being Taken Seriously Questionnaire-Patient version (BTSQ-P) [10]. It was found that it is possible to define and measure being taken seriously by means of a one-factor solution covering eight items.…”
mentioning
confidence: 78%
“…PCC is implemented to reduce patients' disadvantage and involves respect for their personal needs, mutual agreements, patient participation and the perspective that the patient is more than her/his disease [7]. PCC, as a core competence among health care professionals, has been investigated previously and recently there has been emphasis on the PCCL [8][9][10]. The intention is to measure experiences among patients and their significant others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation